Investigation of overlap effects in abrasive water jet strengthening of carburized 18CrNiMo7–6 alloy steel - Lan-rong Liu; Bao-cheng Sun; Guang-tao Xu; Yong-tao Ma; Ming-hao Zhao; Zhen-ye Zhao (Materials Research Express)
The application of abrasive water jet (AWJ) technology is prevalent in enhancing the surfaces of intricate and high-strength components, thereby augmenting their resistance to fatigue. In this context, the distribution of energy plays a pivotal role in the strengthening process, necessitating a thorough examination of its uniformity. The uniformity of energy distribution is primarily influenced by several key parameters, including particle performance metrics, the distribution of particle velocities, their spatial arrangement, and the degree of overlap. This research presents theoretical models for both single-pass and multipass overlap energy distribution, taking into account the spatial and velocity distributions of the particles. Moreover, the study establishes the ratio of the energy differential to the maximum energy within the overlap region as a benchmark for assessing energy distribution uniformity. Leveraging the correlation between deformation and energy, the theoretical model was validated using 18CrNiMo7–6 alloy steel. The findings reveal that the maximum theoretical deformation from a single pass closely matches experimental data, with a discrepancy of less than 6%. Furthermore, the discrepancies between theoretical and experimental peak and trough values post-multipass overlap are found to be in good concordance. The model proposed herein can be effectively utilized to determine the overlap, thereby informing practical engineering applications.